Multi-site measurement for energy application of small distributed wind farm in complex mountainous areas - Mingjin Zhang; Jingyu Zhang; Yongle Li; Jiaxin Yu; Jingxi Qin; Kai Wei; Lili Song (Energy Reports, 2020)
As a clean and highly valuable renewable energy, wind energy has gradually become an important branch of energy technology. By means of measurement methods, the wind characteristics, energy applications for distributed wind energy source (DWES) in six sites in Henduan Mountains and economic evaluation are investigated. According to the results, the wind characteristics including wind speed and wind direction in mountainous regions are affected significant by topography. Wind speed is season-dependent, while the mean wind direction is not. The maximum wind speed occurs in spring, the minimum wind speed occurs in summer. As for extreme value distribution, the wind data in mountainous areas are more in line with Frechet distribution type. By using Weibull distribution function, Weibull parameters are calculated and energy potential are estimated with five methods. Estimation methods suitable for coastal areas can also be used for energy assessment in mountain environments. The maximum wind power density is over 200 W/m2, occurred in Zanli site, while the minimum value is less than 10 W/m2 in Yimen-A. Similar to mean wind characteristics, wind power density shows strong seasonality, with the maximum value in spring and the lowest value in summer. In addition, power generation facilities should be built in valleys or on the top of the mountain, and should not be built in the flat land surrounded by mountains. And the total cost of 1kWh wind-generated electricity is 0.305 CNY/kWh and 0.406 CNY/kWh with different type of wind turbine.
Keywords: 330; Complex mountainous region; Extreme value analysis; Mountainous wind characteristics; Multi-site measurement; Weibull distribution; Wind energy